Evaluación metodológica del proceso químico extractivo de quitina y quitosano en latinoamérica (2020)
Chitin and chitosan are biopolymers obtained from the exoskeleton of crustaceans and insects, their extractive process is booming due to the diversity of industrial, pharmaceutical, agricultural applications, among others. For its obtainability, the variety in methodological processes, are based on the empirical analysis of each author according to their extraction conditions. In general, there is no standardized manual or guideline for such an action, which allows the researcher to obtain higher quality products. This by an evaluation of criteria to articles related to the subject in Latin America, the result of which was the selection of 4 methodologies which were carefully analyzed according to the extraction phases, percentage of efficiency in extraction and quantity-quality ratio, thus finding that the best result methodology was: demineralization with HCl 0.6N (11:1) for 3 hours at 28oC, deproteinization with NaOH solution 1% for 24 hours at 28oC and deacetylation with NaOH 50% for 2 hours at 60-100o C. The objective of this research is to determine a methodology whose characteristic and expected results are the highest, thus serving as a basis for the standardization of protocols for other studies involving the extraction of chitin and chitosan.